Soil CO2 Emission Largely Dominates the Total Ecosystem CO2 Emission at Canadian Boreal Forest - Bhanja, Soumendra N.; Wang, Junye; Bol, Roland (Frontiers in Environmental Science, 2022)
The natural carbon dioxide (CO2) emission from the ecosystem, also termed as the ecosystem respiration (Reco), is the primary natural source of atmospheric CO2. The contemporary models rely on empirical functions to represent decomposition of litter with multiple soil carbon pools decaying at different rates in estimating Reco variations and its partitioning into autotrophic (Ra) (originating from plants) and heterotrophic (originating mostly from microorganisms) respiration (Rh) in relation to variation in temperature and soil water content. Microbially-mediated litter decomposition scheme representation are not very popular yet. However, microbial enzymatic processes play integral role in litter as well as soil organic matter (SOM) decomposition. Here we developed a mechanistic model comprising of multiple hydro-biogeochemical modules in the soil and water assessment tool (SWAT) code to explicitly incorporate microbial-enzymatic litter decomposition and decomposition of SOM for separately estimating regional-scale Ra, Rh and Reco. Modeled annual mean Reco values are found varying from 1600 to 8200 kg C ha-1 yr-1 in 2000-2013 within the boreal forest covered sub-basins of the Athabasca River Basin (ARB), Canada. While, for the 2000-2013 period, the annual mean Ra, Rh and soil CO2 emission (Rs) are varying within 800-6000 kg C ha-1 yr-1, 700-4200 kg C ha-1 yr-1 and 1200-5000 kg C ha-1 yr-1, respectively. Rs generally dominates Reco with nearly 60-90% contribution in most of the sub-basins in ARB. The model estimates corroborate well with the site-scale and satellite-based estimates reported at similar land use and climatic regions. Mechanistic modeling of Reco and its components are critical to understanding future climate change feedbacks and to help reduce uncertainties particularly in the boreal and subarctic regions that has huge soil carbon store.